Macro-charcoal as evidence for wildfire events during the Valanginian–Hauterivian and Barremian? (Rajmahal Formation, Lower Cretaceous) in the Raniganj Coalfield, West Bengal - Murthy, Srikanta; Jasper, André; Uhl, Dieter (Cretaceous research, 2023)
Evidence for palaeo-wildfires occurs widespread in continental Cretaceous deposits all over the world and large parts of the Cretaceous are considered as high-fire periods of the Earth's history. However, published evidence for such Cretaceous wildfires is unevenly distributed, not only from a stratigraphical but also palaeogeographical point of view. Published evidence for earliest Cretaceous (Berriasian–Barremian) wildfires is much rarer than for the later parts of the Cretaceous (Aptian–Maastrichtian) and the majority of publications on this subject deal with evidence from the northern hemisphere, whereas evidence from the southern hemisphere (=former parts of the supercontinent Gondwana) has so far only rarely been published. Here we present evidence, in form of macroscopic charcoal fragments, for the occurrence of wildfire events during deposition of the Valanginian–Hauterivian as well as Barremian? strata of the Rajmahal Formation in the Raniganj Coalfield, West Bengal, India. These occurrences represent so far the oldest Cretaceous records for palaeo-wildfires on the Indian part of the former super-continent Gondwana, adding further proof that wildfires were globally distributed during this period.